Lecturers’ perception on the implementation of approaches to teaching literature in EFL classrooms - Febriani, R. Bunga; Rukmini, Dwi; Mujiyanto, Januarius; Yuliasri, Issy (Studies in English language and education, 2022)
The selection of appropriate approach(es) to teaching literature in EFL classrooms becomes a necessity that they can result in good performance of the students, both in their critical thinking aspect and their language proficiency. The problem appears when the lecturer does not implement a suitable approach to literary analysis when teaching literature to the EFL students. These problems led to the student’s inability to perform as expected. The present study examines how lecturers perceive the implementation of approaches to teaching literature in EFL classrooms and their relations to improving the students’ reflective writing skills as the manifestation of the student’ responses to the literary works. Among the approaches studied were the Language-based approach, the Reader-Response approach, and the Philosophical approach. The study was carried out on six lecturers teaching the Literary Criticism course in the EFL classrooms at the university level. A questionnaire was distributed to the lecturers teaching this course at a university in Semarang, Indonesia, containing eight-question items regarding how they perceive the literary approaches and how effective they used them in improving the students’ reflective writing skills, in encouraging the students to think critically about the events in literary works and in relating the readings to some aspects of their own lives. The study revealed that each literary analysis approach in teaching literature has its benefits and characteristics. The study results also showed that each approach has its strengths and weaknesses that differ from one another.